Refugees in the Imperial Order of Things : Citizen, Subject, and Polish Refugees in Africa (1942–50) - Lingelbach, Jochen (Africa Today, 2022)
Examining the case of some nineteen thousand Polish refugees in British colonial Africa, this article challenges the Eurocentric historiography of the post–World War II international refugee regime. These Poles, after being hosted by the colonial governments first, eventually came under the mandate of emerging UN refugee organizations that treated Europeans as internationally recognized refugees everywhere in the world. In contrast, fleeing Africans (and Asians) did not fit this category. This distinction had more to do with imperialism and race than with any geographic limitation. Conceptually, the refugee regime rests on the differentiation of refugees and national citizens, while imperial rule differentiated between European citizens and colonized subjects. I want to complicate this by emphasizing that the international refugee regime emerged in a largely imperial world signified by a tripartition into citizen, subject, and European refugee.